Analisa Atas Besaran Underground Economy di Indonesia Pada Tahun 2016-2021 Dengan Pendekatan Moneter - Dimas Andi Wirawan (Cakrawala Repositori IMWI, 2023)
This study aims to analyze and determine the magnitude of the value of underground economy activities in Indonesia in the first quarter of 2015 to the fourth quarter of 2021. The method in this study is quantitative analysis using multiple linear regression equations estimated by the least squares method (Ordinary Least Square). The regression equation model used is a monetary approach model, which is a measurement of the magnitude of the underground economy based on the sensitivity of demand for currency. The bound variables used are the amount of demand for currency while the free variables include tax burden, opportunity costs, inflation, nominal Gross Domestic Product (GDP) and financial innovation. The result of this study is that the value of underground economy activities in the research period shows fluctuating values, with a range of values ranging from 127,384 billion to Rp. 625,919 billion The average calculation in that period shows a value that reaches Rp. 325,127 billion or equivalent to 18.2% of Nominal GDP. The novelty of this study is to update the data until 2021 and make adjustments to the variables and models used by the previous study.